Heat and Freshwater Transport by Mesoscale Eddies in the Southern Subpolar North Atlantic ... - Muller, Vasco; Kieke, Dagmar; Myers, Paul G.; Pennelly, Clark; Steinfeldt, Reiner; Stendardo, Ilaria (University of Alberta Library, 2019)
A new data set of temperature and salinity fields reconstructed from satellite altimetry data between January 1993 and April 2014 is combined with satellite observations of mesoscale eddies in the subpolar North Atlantic between 40°N–55°N and 43°W–20.5°W. The data set is used to calculate the meridional heat and freshwater transports related to the propagation of eddies crossing 47°N, a latitude close to the boundary between the subpolar and the subtropical gyres. The largest heat and freshwater transports by eddies are observed in the western part of the Newfoundland Basin. Around 35–45% of the heat and freshwater transports by eddies across 47°N stem from individual isolated eddies with large thermohaline signatures. Northward moving cold and fresh cyclonic eddies carrying subpolar water from the Western Boundary Current make a considerable contribution to the overall heat and freshwater transport by eddies crossing 47°N. While the transport by individual eddies is negligible compared to the transport by ...